Risky Sexual Behavior From A Cultural Perspective Among Youth: Systematic Review - Nurmisih, Nurmisih; Asrial, Asrial; Asyhar, Rayandra; Kalsum, Ummi (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2024)
Background : Adolescence is an important stage for starting high-risk behavior, including in the realm of sexuality. Race or ethnicity is an important factor related to sexual behavior. Perpose: to evaluate the behavior of adolescents in engaging in high-risk sex from the perspective of their respective ethnic cultures. Methods : This systematic review followed the 2020 version of the PRISMA guidelines. The initial search was conducted from April to June 2023. Search sources from 4 databases, using 5 keywords: adolescent, sexual behaviour, high-risk behaviour, sexual risk, and reproductive behaviour. Criteria: observational study, using English, 2000 to 2023, school adolescent population. There were 1,492 papers found after searching the database. The systematic review contained the final 11 research following screening and eligibility determination. Results : Overall, high-risk sexual behavior appears to demonstrate no significant differences among Latino, Hispanic, European, and American adolescents. However, in Asia, pre-marital sex remains highly stigmatized in contrast to its acceptance in Europe and America. Acculturation emerges as a critical predictor contributing to increased high-risk sexual behavior. In Latin adolescents, a lack of compliance with family ties (Familismo) strongly correlates with high-risk sexual behavior. Moreover, in Hispanic adolescents, paternal discipline seems to have a greater association with high-risk sexual behavior compared to maternal discipline. Notably, there were no discernible differences among ethnicities concerning gender, indicating that males across these groups were more prone to engaging in high-risk sexual behavior. Conclusion. Sex education is a prevalent topic among Western societies, primarily aimed at curbing unsafe sexual behavior to prevent venereal diseases. In contrast, Asian cultures still regard sex education as taboo, placing emphasis on preventing extramarital sexual activity.